Audiovisual policies and international trade: The case of Italy - Simona Andreano; Lelio Iapadre (Hamburg Institute of International Economics (HWWA), 2003)
This paper reviews Italian audiovisual policies, in order to assess their impact on the international position of domestic cinema and television producers. Italian audiovisual policies are characterised by a rich set of institutions, regulations and support tools, whose complexity sometimes causes problems of overlapping jurisdictions among different authorities and agencies. Their degree of market access restrictiveness appears to be relatively high, especially considering the discrimination between European and non-European producers. The economic performance of the Italian audiovisual sector has been relatively weak in the nineties, particularly for what concerns the competition with foreign producers. On the other hand, the econometric exercise presented in section 5 seems to show that, at least in the cinema sector, public subsidies have a positive impact on the domestic market share of Italian producers. This preliminary conclusion is however not enough to justify a positive assessment of Italian audiovisual policies. Many important issues require further investigations. The problems and the data presented in this paper seem to confirm the need to reform the strategy and the tools of public intervention in the audiovisual sector.
Keywords: 330